2001
DOI: 10.1007/s004240100586
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by nitric oxide

Abstract: Nitric oxide (NO) modulates transcription factors that bind specific cis-regulatory DNA responsible for coordinating the spatial and temporal patterns of gene expression that are initiated by a changing microenvironment. In this way NO helps to orchestrate gene transcription and forms the basis of functional cell responses to accommodate metabolic requirements and to coordinate endogenous defense mechanisms against a variety of stress and disease conditions. There is marked overlap between the signalling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 47 publications
4
83
0
1
Order By: Relevance
“…15,28,29 To identify NO-regulated genes that may be functionally important in the context of cardiac hypertrophy and failure, we analyzed the expression profile of 1176 genes in cardiac myocytes stimulated with the prohypertrophic polypeptide ET-1 in the presence or absence of the NO donor SNAP. Several genes were identified that were differentially regulated by NO ( Table).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,28,29 To identify NO-regulated genes that may be functionally important in the context of cardiac hypertrophy and failure, we analyzed the expression profile of 1176 genes in cardiac myocytes stimulated with the prohypertrophic polypeptide ET-1 in the presence or absence of the NO donor SNAP. Several genes were identified that were differentially regulated by NO ( Table).…”
Section: Discussionmentioning
confidence: 99%
“…2,11 Studies in NOS2-deficient and NOS2-overexpressing mice indicate that upregulation of NOS2 is detrimental and may increase mortality in heart failure. [12][13][14] The effects of NO in various cell types and tissues are mediated, in part, via changes in gene expression, 15 raising the possibility that transcriptional effects of NO may play a role in cardiac hypertrophy and failure as well. Little is known, however,…”
mentioning
confidence: 99%
“…It has previously been suggested that NO produced by iNOS possess an influence on eNOS and nNOS expression at a transcriptional regulation level, as shown for a great number of genes including those for iNOS itself (see Pfeilschifter et al 2001). Furthermore, LPS-and cytokine-influenced variations in the regulation of eNOS mRNA expression have also been indicated (cf.…”
Section: Alterations In Nnos By MD Cells As Part Of Compensatory Intementioning
confidence: 91%
“…Moreover, NO may also inhibit the expression of integrins, such as CD11a/CD18, in neutrophils (Banick et al 1997, Grisham et al 1998). Since NOS2 is involved in peroxynitrite-dependent tyrosine nitration (Sato et al 2000, Yeh et al 2007, it also regulates chemokine production and affects the inflammatory response mediated by IP-10, MCP-1, MIP-1a and MIP-2, and IL-8 (Mach et al 1999, Pfeilschifter et al 2001.…”
Section: No and The Immune Responsementioning
confidence: 99%